Soft x-ray spectroscopic investigation of ferromagnetic Co-doped ZnO - MCGUINNESS, CORMAC; LUNNEY, JAMES; PATTERSON, CHARLES; VENKATESAN, MUNUSWAMY; COEY, JOHN (My University, 2006)
The electronic properties of cobalt-doped ZnO were investigated through site-selective and element-sensitive x-ray-absorption spectroscopy in the vicinity of the Co L2,3 edge, the oxygen K edge, and at the Zn L3 edge. The spectroscopic measurements of the ferromagnetic cobalt-doped ZnO films appear to have additional components in the O K edge x-ray-absorption spectrum not observed in the undoped films. The observed features may derive from both hybridization with unoccupied Co 3d states and also from lattice defects such as oxygen vacancies. Only minor changes in the Zn L3 edge spectra were observed. These observations are consistent with a polaron percolation model in which the ferromagnetic coupling is mediated by shallow donor electrons trapped in oxygen vacancies and couples the Co atoms substituted on Zn sites in the hexagonal wurtzite ZnO structure.
PUBLISHED
Keywords: Physics